A technique for in situ X-ray computed tomography of deformation-induced cavitation in thermoplastics. (November 2020) - Olufsen, Sindre Nordmark; Tekseth, Kim Robert; Breiby, Dag Werner; Clausen, Arild Holm; Hopperstad, Odd Sture
Abstract: Deformation-induced cavitation influences the mechanical response of polymeric materials, but acquiring in situ measurements of the spatial evolution of cavities has typically necessitated the use of synchrotron radiation sources. The objective of this study is to develop and demonstrate a method allowing for in situ measurements of deformation-induced cavitation in axisymmetric polymer specimens, using a home-laboratory X-ray computed tomography setup. The method is demonstrated by assessing deformation-induced cavitation of mineral-filled PVC in a repeated loading-unloading experiment. A temporal resolution of about 3 s is obtained by exploiting the axisymmetry of notched round tensile specimens. The evolution of relative density was captured throughout the experiment, revealing an interplay between void nucleation and void growth. Combined with surface deformation measurements obtained by digital image correlation, the present technique yields data suitable for calibration and validation of material models. Highlights: The technique allows for in situ measurements of deformation-induced cavitation in axisymmetric polymer specimens, using a home-laboratory X-ray computed tomography setup. By exploiting the axisymmetry of the tensile specimen, a temporal resolution in the order of seconds is achieved. The spatio-temporal evolution of relative density was measured for a notched tensile specimen made of mineral-filled PVC, subjected to a loading-unloading procedure. The described experimental procedure provides data suitable for material model development and validation.